Platygonia Melichar, 1925 (Insecta: Hemiptera: Cicadellidae: Cicadellini): a new species from the Brazilian Amazon Rainforest, key to species of the genus, and notes on P. undecimmaculata (Fowler, 1899) - Quintas, Victor; Pecly, Nathalia H.; Carvalho, Stéphanie R.; Mejdalani, Gabriel (European Journal of Taxonomy, 2022)
A new species of the Neotropical genus Platygonia Melichar, 1925 is described and illustrated from the municipality of Ipixuna, State of Amazonas, Northern Brazil. Platygonia nigra sp. nov. can be distinguished from the other species of the genus by the following combination of features: (1) dark brown to black ground color of dorsum; (2) presence of a white to pale yellow spot at the distal portion of corium; (3) male pygofer with a conspicuous diagonal cleft; (4) connective Y-shaped, keeled, with the stem longer than the arms; and (5) aedeagus with an unpaired basiventral process directed anteriorly. This is the first record of the genus from the Brazilian Amazon Rainforest. Notes on P. undecimmaculata (Fowler, 1899), which is a taxon of uncertain taxonomic position, a key to the species of Platygonia, and a map showing their distribution are added.